Immunogenicity of Anti-TNF-α Biotherapies: II. Clinical Relevance of Methods Used for Anti-Drug Antibody Detection - Bendtzen, Klaus (Frontiers in Immunology, 2015)
Immunogenicity of biopharmaceuticals is complex and influenced by both structural and pharmacological factors, and by patient-related conditions such as disease being treated, previous and concomitant therapies and individual immune responsiveness. Essential for tailored therapeutic strategies based on immunopharmacological evidence from individual patients (personalized medicine) is the use of assays for anti-drug antibodies (ADA) that are accurate and relevant in the clinical setting. This paper discusses immunogenicity of genetically engineered immunoglobulins directed against tumor necrosis factor-α (TNF). Emphasis will be on commonly used methods for detection of ADA in human serum including issues that question the clinical applicability of these methodologies. The use of dubious assays for ADA in a clinical context may not only contribute to confusion as to the importance of drug immunogenicity, it may also prevent development of safe and cost-effective ways of using biological TNF-antagonists.